Aspects of Distribution, Abundance, Habitat, and Life History of the Caddo Madtom (Noturus taylori), a Narrow Endemic of the Ouachita Highlands - Brittany L. McCall; Brook L. Fluker (Southeastern Fishes Council Proceedings, 2023)
The Caddo Madtom, Noturus taylori, is a small catfish endemic to the Ouachita Mountain ecoregion in Arkansas, with habitat altered by land use practices and reservoir dams. We examined aspects of distribution, abundance, habitat, and life history of N. taylori during seasonal sampling from winter 2016 through fall 2017. Our sampling data were concordant with previous studies that suggested N. taylori is more widespread and has higher catch per unit effort in the Caddo River drainage when compared to the upper Ouachita River drainage. We did not detect N. taylori in the Little Missouri River drainage, where it is presumed extirpated. A total of 370 individuals ranging from 14–76 mm (mean = 45.1 mm) standard length (SL) were collected during seasonal samples. Length-frequency analyses estimated a maximum age of 3 years for N. taylori, and we identified three discernable age classes with the emergence of young-of-year (age 0 cohort) in summer: age 0 (up to ~40 mm SL); age 1 (~41-60 mm SL); and age 2+ (>60 mm SL). Sites where N. taylori was captured had an average depth of 20.6 cm, an average base velocity of 0.18 m/sec, and were dominated primarily by a mix of gravel, pebble, and cobble. Despite the relatively higher abundances of N. taylori in the Caddo River, we recommend that long-term, periodic monitoring of N. taylori would be an important conservation tool to assess potential future changes in distribution, habitat, occurrence, and abundance. Future studies that implement occupancy and habitat suitability modeling are needed to better understand suitable and preferred habitat of N. taylori.
Keywords: Ictaluridae; CPUE; length-frequency analysis; ELEFAN; endemism